Characterising marine mollusc exploitation in the eastern African Iron Age: Archaeomalacological evidence from Unguja Ukuu and Fukuchani, Zanzibar. (25th March 2018) - Faulkner, Patrick; Harris, Matthew; Ali, Abdallah K.; Haji, Othman; Crowther, Alison; Horton, Mark C.; Boivin, Nicole L.
Abstract: Molluscan remains from archaeological contexts have the potential to provide information related to a range of issues, including but not limited to settlement and economic structures, and local environmental conditions. Shell deposits are ubiquitous along the eastern African coast and offshore islands, with previous archaeological research highlighting the prevalence of these deposits in conjunction with providing some discussion on the variable contribution or role of molluscs within the economy. In general, marine molluscs have been viewed as a secondary or fall-back resource with largely opportunistic harvesting in the intertidal zone. In addition, there is a general expectation that there would be significant variability in exploitation depending on settlement structure, the availability of domesticates, and with status differences. With few exceptions, however, the scale and resolution of archaeomalacological analyses across the broader region have tended to be relatively coarse, making it difficult to adequately assess these interpretations. Here we consider these issues based on detailed analyses of the sites of Unguja Ukuu and Fukuchani situated on the island of Unguja (Zanzibar), providing an assessment of the relative importance of the exploited taxa and ecological niches, in combination with species richness and diversity. These analyses provide a comparative framework for other sites in the region, and a baseline understanding of human interactions with coastal environments through molluscan exploitation.